2012
DOI: 10.1299/jamdsm.6.1222
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on the Minimum Quantity Lubrication in High-Speed Helical Milling of Ti-6Al-4V

Abstract: The objective of the present work was to study the effect of the application of minimum quantity lubrication (MQL) in high-speed helical milling of Ti-6Al-4V compared with dry and flood coolant (wet) condition. The single factor experiment to study the relationship between cutting force, hole surface roughness and cutting parameters under various coolant-lubricant conditions were implemented. Tool life under various cooling conditions and fixed moderate cutting parameters have also been studied. Uniform flank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Brinksmeier et al(2011)conducted a comprehensive analysis on the cutting force, cutting temperature and surface integrity in the helical milling and drilling of aluminum alloy/ CFRP/ titanium laminate, the results showed that helical milling technique could effectively reduce cutting force, cutting temperature and improve the hole quality. The dynamics in helical milling of titanium alloy was analyzed , and the cutting force, tool wear and hole quality state were detailedly discussed (Qin, et al,2012). Cutting force modeling in the helical milling process were simulated (Liu, et al, 2012), hole-surface topology and surface quality in helical milling process were simulated (Li and Liu,2013).…”
Section: Fig1 Helical Milling Processmentioning
confidence: 99%
“…Brinksmeier et al(2011)conducted a comprehensive analysis on the cutting force, cutting temperature and surface integrity in the helical milling and drilling of aluminum alloy/ CFRP/ titanium laminate, the results showed that helical milling technique could effectively reduce cutting force, cutting temperature and improve the hole quality. The dynamics in helical milling of titanium alloy was analyzed , and the cutting force, tool wear and hole quality state were detailedly discussed (Qin, et al,2012). Cutting force modeling in the helical milling process were simulated (Liu, et al, 2012), hole-surface topology and surface quality in helical milling process were simulated (Li and Liu,2013).…”
Section: Fig1 Helical Milling Processmentioning
confidence: 99%
“…In the last decades optimization of such process has been carried out considering different issues, such as cutting lubrication (Qin et al, 2012), environmental impact (Campatelli et al, 2015), surface integrity (Duan and Hao, 2014). However performances of this technology are still limited by self-excited chatter vibration occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Relative experimental research works on helical milling technique were successively set up, in which cutting force, tool wear, and hole quality state in helical milling of different material were discussed in details [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%